The paradoxical self: duality and ambiguity in the works and lives of Oscar Wilde and Morrissey - Adamskich, Karolina (Scripta Neophilologica Posnaniensia, 2021)
Oscar Wilde’s and Morrissey’s lives seem to be full of contradictions. Their art constitutes a reaction against materialism, traditional lifestyle and social standards, as well as defence of individualism and freedom of thought. So far, their works have been analysed only from a very limited perspective of the tension between aesthetics and ethics. Nevertheless, it is worth mentioning that what prevails in their art is the state of ambivalence and ambiguity in relation to the issues connected with religion and morality, innocence and experience, life and death. This article aims at demonstrating multiplicity of personalities of the artists mentioned and ethical ambivalences of their works. Taken together, Wilde and Morrissey’s creative outputs present a clash between different spheres of life, the divided consciousness and the split between body and soul. Thus, the oscillation between opposite standpoints and values excluding each other is not only the result of the artists’ personal experience but it may symbolise the paradox and absurdity of the human existence as well.